Current Account Imbalances and the Euro Area: Alternative Views - Ronny Mazzocchi; Roberto Tamborini (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
The crucial role of current account imbalances (CAI) is widely acknowledged in the consensus narratives of the European crisis that followed the Great Recession. On the basis of this interpretation, new EU initiatives arose, in particular the so-called "Six Pack" in 2011 and the establishment of the European Semester procedure to improve policy coordination in the EU beyond fiscal matters. This package includes the Macroeconomic Imbalances Procedure (MIP), which broadens the EU economic governance framework to include the surveillance of unsustainable macroeconomic trends. Although the widening of the CAI in the Euro Area is a matter of fact, and the consensus narrative contains elements of truth, alternative views have been put forward on three main issues: i) their relevance, ii) their causes and connection with the crisis, and iii) their policy implications. The aim of this paper is to examine these controversial points about the causes, meaning and consequences of CAI, and discuss the alternative policy prescriptions that emerge.
Keywords: 330